-4(7-x)(7+x)=4x(x-5)

Simple and best practice solution for -4(7-x)(7+x)=4x(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(7-x)(7+x)=4x(x-5) equation:


Simplifying
-4(7 + -1x)(7 + x) = 4x(x + -5)
Multiply (7 + -1x) * (7 + x)
-4(7(7 + x) + -1x * (7 + x)) = 4x(x + -5)
-4((7 * 7 + x * 7) + -1x * (7 + x)) = 4x(x + -5)
-4((49 + 7x) + -1x * (7 + x)) = 4x(x + -5)
-4(49 + 7x + (7 * -1x + x * -1x)) = 4x(x + -5)
-4(49 + 7x + (-7x + -1x2)) = 4x(x + -5)
Combine like terms: 7x + -7x = 0
-4(49 + 0 + -1x2) = 4x(x + -5)
-4(49 + -1x2) = 4x(x + -5)
(49 * -4 + -1x2 * -4) = 4x(x + -5)
(-196 + 4x2) = 4x(x + -5)
Reorder the terms:
-196 + 4x2 = 4x(-5 + x)
-196 + 4x2 = (-5 * 4x + x * 4x)
-196 + 4x2 = (-20x + 4x2)
Add '-4x2' to each side of the equation.
-196 + 4x2 + -4x2 = -20x + 4x2 + -4x2
Combine like terms: 4x2 + -4x2 = 0
-196 + 0 = -20x + 4x2 + -4x2
-196 = -20x + 4x2 + -4x2
Combine like terms: 4x2 + -4x2 = 0
-196 = -20x + 0
-196 = -20x
Solving
-196 = -20x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '20x' to each side of the equation.
-196 + 20x = -20x + 20x
Combine like terms: -20x + 20x = 0
-196 + 20x = 0
Add '196' to each side of the equation.
-196 + 196 + 20x = 0 + 196
Combine like terms: -196 + 196 = 0
0 + 20x = 0 + 196
20x = 0 + 196
Combine like terms: 0 + 196 = 196
20x = 196
Divide each side by '20'.
x = 9.8
Simplifying
x = 9.8

You can always share this solution

See similar equations:

| (x+5)(x+7)=8 | | 12t+12=4t-4 | | 5p+4q-p-6q= | | 15x-39=11x-9 | | 8x(x-9)+(7-x)8x=64 | | 26=-0.6x+43 | | 3x+10/3=135-10/3 | | x(6x^2-y-1)dy+2ydx=0 | | x+7=-31 | | (-2y+5)(-2y+5)=0 | | (4-v)(4v+3)=0 | | -3k*7t= | | 17x-23=74+81 | | Y+1(28+3)-20=16 | | 2/3(9)-y=4 | | 5x^2-9k-6=0 | | 1/2n-2/3=5/6 | | 20x^2+x+12=0 | | y=2x(x-4) | | 8/4=2 | | 8/4=1x+1x | | 5-x-6y=0 | | Y+1(28+2)-20=16 | | 5x+3/3=26 | | 2x+7=32+78 | | 5x-19=-89 | | .5(x+3)=6 | | 8n=24+2x | | (6x^6)/7•28/(9x^2) | | y=-3x^2-30x-67 | | (b+4)(b+4)=100 | | 77.8(x-2)=0.2+24.4 | | 88+9y=-2 | | -0.6(3v-15)=0.4(3-5v) | | S/6=7/3 | | -6=6+2u | | (7-y)(7-y)=0 | | 4/x=0.66 | | 2x+x+x+10=84 | | 5-2/x=12 | | (5x+4)(5x+4)=81 | | 65=0.2(w-10(4)) | | 2x-3(x+r)=-5 | | 49-14y-y^2=0 | | 65=0.2(w-10e) | | X=3t+4 | | S=0.2(w-10e) | | (x+8)+(13x-7)=15 | | 23x-3=78 | | (2-x)(x^2-9)=0 | | 28x-7=26x-5 | | ln(2x+5)=ln(6x-1) | | 5-3k+7-9k= | | -n^2+12n-63=-4n^2 | | 5r(r-8)=0 | | 49-2=3a-10a | | -4+5y=-14 | | 13x^2-7100x=420000 | | -5-4y=3 | | 13x^2-2900x=210000 | | G+4h=180 | | 4+2(x+10)=50 | | -22=8y+6(y+8) | | 4x^2=-25+20x | | 8-58=-3(-3m)-8(2m)+2m |


Related pages


derivative cos 2x360-268180-138xy xyz24.99 in dollarscot 2asin 2x sinx cosxderivative of 3 cos x2iz0.1875 as fraction4000 dollars in poundsderivative sin4xsin of arctan8x287-111solutions to inequalities calculator1.0e-3factoring calculator step by stepwhat is the gcf of andprime factors of 198factor 5x 2 3x-2294.9what is the prime factorization of 61solve 2x y 7complex fractions calculator with stepscos3x sin2xderivative of tan 2xtanx secx 2cosxhow to write 0.25 as a fraction2x 2 graph3x-3y 9natural log derivative calculatorcosx tanx299-100x 2y 6 solve for ysqrt 3 3factorization of 19625kg lb6x 2y 8graph sin 4x4x 5y 20what is 3y3y 2x 9derivative of ln e 2xwhat is the prime factorization of 2401.8.6cosx cosx sinxcommon multiples of 9 and 7multiplying mixed fractions calculatorderivative sin4x2cos 2x 14x 2y 9simplify square root of 15015-30-5x squared 4x2xy xywhat is 5 of 21what is 6 of 20factor 2x 2 15x 7simplify the square root of 243prime factorization 88differentiate e cos xprime factorization of 74derivative tanxlcm finderprime factorization of 792sinx sin2xderivative of ln2solve y 2x 5derivative of 9xy 4x graph6x 4y 24prime factorization of 588cotg x1955 in roman numeralstanx secx 2cosxsimplify square root 96